PENERAPAN MUROTAL SURAT AR-RAHMAN UNTUK MENSTABILKAN STATUS HEMODINAMIKA PASIEN STROKE HEMORAGIK DI RSUD KARAWANG - Dina Hartini; Yumi Dian Lestari (Ensiklopedia of Journal, 2023)
Stroke is a type of non-communicable disease (PTM) and is included in the neurological function disorders caused by Cardio Vascular Diseases (CVD). This disease is mostly caused by blockages that block blood flow to the brain (Alfianita, 2020, in (Irman, 2021). Strokes are divided into two types, namely ischemic strokes caused by blockages in blood vessels (platelets, emboli) and hemorrhagic strokes caused by a ruptured blood vessel in the brain (Auryn, 2017 in (Nurlaily, 2021) The design used was a quasy experiment. The study respondents were 80 respondents. Based on the results of bivariate analysis on clients with hemorrhagic strokes before the Al-Rahman letter murotal therapy, the test results obtained statistically the average value was 1.51, while after being given the Al-Rahman letter murotal therapy, the average value was 1.65 and the mean difference was 1.9, while the average blood pressure before murotal therapy was 180/100 mmHg, after murotal therapy 160/90 mm Hg, these results showed a statistically significant difference before and after the action was given, this indicates the effect of murotal therapy Surah Ar-Rahman to stabilize the hemodynamics of stroke patients. From the results of this study murotal therapy with the letter of Ar-Rahman to stabilize hemodynamics: blood pressure. So it can be concluded that there is a relationship between murotal therapy and hemodynamic changes in blood pressure in stroke patients   Keywords: Stroke, Murotal Qur'anic Therapy, Pain.